Ocular Risk Factors for Age-related Macular Degeneration: The Los Angeles Latino Eye Study (LALES) - Fraser-Bell, Samantha (2010)
PURPOSE: To assess the association of ocular factors and age-related macular degeneration (AMD) in Latinos. DESIGN: Population-based, cross-sectional study of 6357 self-identified Latinos aged 40 years and older. METHODS: Ophthalmic examination included subjective refraction, measurement of axial length, evaluation of iris color, Lens Opacities Classification System II (LOCS II) grading of cataracts, and stereoscopic macular photographs for AMD lesions. Generalized estimating equation analysis incorporated data from both eyes to estimate odds ratios adjusted for covariates. RESULTS: After controlling for confounders (age, gender and smoking), prior cataract surgery was associated with advanced AMD (OR: 2.8, 95% CI 1.0, 7.8), increased retinal pigment (OR: 1.6, 95% CI 1.0, 1.5) and retinal pigment epithelial depigmentation (OR: 2.2, 95% CI 1.1, 4.4). The presence of any lens opacity was associated with soft drusen (OR: 1.2; 95% CI 1.0, 1.5). Longer axial length (per mm) was associated with a decreased odds of soft drusen, increased retinal pigment, and geographic atrophy (GA) (ORs: 0.8 [95% CI 0.7, 0.9], 0.8 [95% CI 0.7, 0.9], 0.7 [95% CI 0.5, 0.9], respectively. Myopia was inversely associated with soft drusen (OR: 0.8; 95% CI 0.7, 1.0). Lighter colored irises were associated with GA (OR: 5.0; 95% CI 1.0, 25.3). CONCLUSIONS: Cross-sectional associations of ocular factors such as cataract, cataract surgery, and refractive errors with early AMD lesions found in Latinos were consistent with those in whites. Additionally, prior cataract surgery was associated with advanced AMD.